Strategy tools in use : new empirical insights from the strategy-as-practice perspective - Berisha Qehaja, Albana (Array, 2020)
This paper examines the usage of strategy tools from the strategy-as-practice perspective. In general, there is a lack of empirical evidence regarding the use of strategy tools, particularly in transition economies. The comprehensive and up-to-date research is mainly concerned with the extent of their use and classification. Thus, academics have already highlighted the need to review their role, importance, and use. Accordingly, this research seeks to bridge the current gap between theoretical constructs and empirical proof of the use of strategy tools in enterprises. The study design used for this research is cross-sectional and data were obtained from 314 enterprises in the Republic of Kosova, using standardized survey-based questionnaires. The purpose of this study is to assess the extent to which strategy tools are used in Kosovan enterprises. It also aims to distinguish their use according to educational background of managers/owners, enterprise size and across different sectors. The results of this study reveal that Kosovan enterprises have a low usage rate of strategy tools. More precisely, the two most used strategy tools are SWOT analysis and vision and mission statements. This paper provides some important insights into strategy tools usage in the Republic of Kosova, as a transition economy. While it provides a better understanding and awareness of strategy tools usage, there are other possible study areas that could offer significant value in future research.